Disciplinary Responsibility of the Legal Translator in UAE Legislation Analytical Study - Alsuwaidi, Sultan; Al Nawayseh, Abdulellah (Journal of Legal Sciences, 2026)
This research on the disciplinary responsibility of legal translators under UAE legislation addresses the legal and ethical aspects that govern the work of translators in legal fields. The study begins by defining the legal translator as a specialist in translating legal documents and judicial texts, requiring the qualifications necessary to understand legal terminology.The research also reviews the applicable laws and regulations in the UAE that regulate the work of translators, such as the Translator Law and regulations concerning public employees.The research distinguishes between disciplinary responsibility (internal) and legal responsibility (external). The former pertains to violations related to professional ethics or conduct, while the latter concerns legal infractions. The study analyzes various types of violations that legal translators may commit, such as errors in translation, misjudgments, and the unauthorized disclosure of confidential information.The research further explains the procedures followed in addressing allegations against translators, starting with investigations and extending to potential sanctions, such as suspension or removal from the list of certified translators.Finally, the research offers recommendations for improving the disciplinary responsibility system, such as the need for enhanced training and professional development for translators, as well as the development of mechanisms to monitor quality assurance.